Understanding Stakeholders’ Perspective on An Innovative Business Model for Pediatric Immunization Records: A Single Case Study - Ramos-Siman, Elaine C.; Orencia, Abrian Joy B. (Future Science / FSH-PH Publications, 2023)
The purpose of this qualitative case study is to explore the potential value of an innovative business model on pediatric immunization record management which will serve as the basis for the development of a digital platform for the use of pediatric consultants and medical secretaries at a private secondary hospital in Quezon City. The study utilized a qualitative case study involving the pediatric consultants and medical secretaries of a private secondary hospital in Quezon City. Qualitative data for this study were gathered through in-depth, semi-structured interviews, focus group discussions, documents, journaling, and observations. Results have shown that pediatric consultants and medical secretaries follow only one way of arranging patients' records which is through alphabetical order using the surname. Many clinics and hospitals still rely on paper-based medical records to document patients' information. All participants shared the same difficulties and sentiments when it comes to the problems they have in the current way they deal with immunization records. Based from the statements of the participants, results revealed that pediatric consultants and medical secretaries support and are in favor of the use of a web-based record management system. However, some participants stated their apprehensions for the security of patient information. Further study that focuses on formal training is recommended to increase the confidence of the healthcare workers in utilizing digital record management systems and intense exploration of the potential challenges in adapting a digitized records management system must be conducted.